A provably secure, shortest, and efficient identity based signcryption technique in the standard model. Issue 1 (3rd October 2022) - Aithekar, Ashutosh; Gupta, Pratik; Dharminder, Dharminder
Abstract: Singcryption is a very important concept to bind confidentiality and authenticity. This is a logical step to reduce both computation and communication costs. The proposed an identity based signcryption that removes the overhead of certificates. The proposed design is provably secure in the standard model (a widely accepted model). Furthermore, the IBSC design uses modified bilinear Diffie‐Hellman inversion and modified strong bilinear Diffie‐Hellman assumption as building blocks of the security. The proposed design is secure, efficient, and shortest to the best of our knowledge. In this design, a user does pairing free computation, and he sends only a triplet on the public channel, that makes it efficient in terms of computation and communication costs.